THE EFFECTIVENESS OF USING DISTANCE LEARNING MEDIA IN THE COVID-19 PANDEMIC AT SDN 50 MANDAU - Atina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Covid-19 pandemic affected psychological conditions and changes in human behavior that covered broader aspects over a longer period of time. It also changed the education system in Indonesia. As a result, teachers and students became familiar with distance learning interactions. The purpose of this article was to see the effectiveness of long distance learning online systems during the Covid-19 pandemic. The Covid-19 pandemic initiated distance learning which utilized various online learning platforms such as google classrooms, zoom cloud meetings, quisziiz, whatsAap group, and other platforms. Each platform had their own functions in supporting the implementation of online learning. Online learning was considered effective to be applied during the Covid-19 pandemic. However, a more varied model was required to keep it interesting to be used in the long term. Learning activities involved a communication process to convey educational messages from teachers to students. It was intended to make the message conveyed by the teacher to be well-received so that it affected the students' knowledge and behavior changes. This implied that the success of a learning activity was very dependent on the effectiveness of the communication process occurred in learning. Therefore, the purpose of this study was to analyze the effectiveness of google classroom as a media for distance learning at SDN 50 Mandau. This study concluded that the implementation of online learning activities was effective and ideal. The online learning run smoothly even though it was not yet ideal. The obstacles faced by students and teachers in online learning included: the availability of internet access, unstable networks, and som supporting devices such as cellphones and laptops